Superelasticity of [001]-oriented Fe42·6Ni27.9Co17·2Al9.9Nb2.4 ferrous shape memory alloys. (15th July 2016) - Karaca, H.E.; Turabi, A.S.; Chumlyakov, Y.I.; Kireeva, I.; Tobe, H.; Basaran, B.
Abstract: The shape memory properties of a ferrous single crystalline alloy, FeNiCoAlNb, were investigated along the [100] orientation by superelasticity tests in both tension and compression. Aging was used to form nano-size precipitates to demonstrate and tailor their shape memory properties. After aging at 700 °C for 3 h, [001]-oriented FeNiCoAlNb shows high compression-tension asymmetry and shape recovery of about 4.5% in tension and 8.8% in compression. The superelastic behavior of [001]-oriented FeNiCoAlNb is weakly temperature dependent due to large transformation strain. FeNiCoAlNb has great potential for temperature independent and large scale actuator applications. Graphical abstract: